1999
DOI: 10.1002/(sici)1522-2586(199909)10:3<404::aid-jmri23>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

First-pass myocardial perfusion imaging and equilibrium signal changes using the intravascular contrast agent NC100150 injection

Abstract: In this phase I clinical study, the new ultrasmall superparamagnetic iron oxide contrast agent, NC100150 Injection (Nycomed AS, Oslo, Norway, a part of Nycomed Amersham), was assessed for first-pass magnetic resonance myocardial perfusion studies and its ability to produce equilibrium signal changes, as a possible indicator of myocardial blood volume. Data were acquired in 18 healthy male volunteers at 0.5 T and 1.5 T. At both field strengths, first-pass studies using T1-weighted sequences were acquired. Long … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…But the use of a T1 cine MR sequence made it possible the localization of the dyskinetic area of myocardium as at lower magnetic fields. 5,24,25 These results differ from previously published studies where quantifiable signal changes were observed in rats, 14,15 healthy volunteers 26,27 or in a model of myocardial infarction induced in pigs. 16 However, those studies were performed at lower magnetic fields whereas r1 relaxivity of the nanoparticles used in the present study was 36 mmol/L Ϫ1 ·s Ϫ1 at 0.5T and 12 mmol/ L Ϫ1 ·s Ϫ1 at 1.5T.…”
Section: Discussionmentioning
confidence: 99%
“…But the use of a T1 cine MR sequence made it possible the localization of the dyskinetic area of myocardium as at lower magnetic fields. 5,24,25 These results differ from previously published studies where quantifiable signal changes were observed in rats, 14,15 healthy volunteers 26,27 or in a model of myocardial infarction induced in pigs. 16 However, those studies were performed at lower magnetic fields whereas r1 relaxivity of the nanoparticles used in the present study was 36 mmol/L Ϫ1 ·s Ϫ1 at 0.5T and 12 mmol/ L Ϫ1 ·s Ϫ1 at 1.5T.…”
Section: Discussionmentioning
confidence: 99%
“…The contrast agent NC100150 Injection has been shown in human to induce both first-pass and steadystate changes in the signal intensity of the myocardium in healthy volunteers (25). A study by Tarlo et al (26) showed the possibility of determining myocardial blood flow quantitatively in pigs with this contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Larger image intensity gradients at the endocardial border were expected to improve the capabilities of automated segmentation algorithms, reducing the uncertainty and need for manual editing [73].…”
Section: Myocardial Perfusion Imagingmentioning
confidence: 99%